Cardiac developmental toxicity and transcriptome analyses of zebrafish (Danio rerio) embryos exposed to Mancozeb - Yongfeng Wang (Ecotoxicology and Environmental Safety, 2021)
Mancozeb (MZ), an antibacterial pesticide, has been linked to reproductive toxicity, neurotoxicity, and endocrine disruption. However, whether MZ has cardiactoxicity is unclear. In this study, the cardiotoxic effects of exposure to environment-related MZ concentrations ranging from 1.88 μM to 7.52 μM were evaluated at the larval stage of zebrafish. Transcriptome sequencing predicted the mechanism of MZ-induced cardiac developmental toxicity in zebrafish by enrichment analysis of Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Ontology (GO). Consistent with morphological changes, the osm, pfkfb3, foxh1, stc1, and nrarpb genes may effect normal development of zebrafish heart by activating NOTCH signaling pathways, resulting in pericardial edema, myocardial fibrosis, and congestion in the heart area. Moreover, differential gene expression analysis indicated that cyp-related genes (cyp1c2 and cyp3c3) were significantly upregulated after MZ treatment, which may be related to apoptosis of myocardial cells. These results were verified by real-time quantitative RT-qPCR and acridine orange staining. Our findings suggest that MZ-mediated cardiotoxic development of zebrafish larvae may be related to the activation of Notch and apoptosis-related signaling pathways.